Benefit of statin pretreatment in prevention of contrast-induced nephropathy in different adult patient population: systematic review and meta-analysis. Issue 1 (14th August 2014) - Singh, Nirmal; Lee, Justin Z; Huang, Jennifer J; Low, See Wei; Howe, Carol; Pandit, Anil; Suryanarayana, Prakash; Lee, Kwan S
Abstract : Objective: Previous studies have suggested that statin pretreatment prevents contrast-induced nephropathy (CIN). However, single randomised trials are limited in their number of patients. This meta-analysis aims to assess the role of statin use in CIN prevention, as well as to determine patient subgroups that will benefit from statin pre-treatment. Methodology: We searched PubMed, EMBASE, Web of science and the Cochrane Central Register of Controlled Trials databases for randomised controlled trials (RCT) comparing statin pretreatment versus placebo for preventing CIN. Our main outcome was the risk of CIN within 1–5 days after contrast administration. Results: Data analysed from nine randomised studies with a total of 5143 patients, where 2559 received statins and 2584 received placebo, showed that statin pretreatment was associated with significant reduction in risk of CIN (MH-RR=0.47, 95% CI 0.34 to 0.64, Z=4.49, p<0.00001). This beneficial effect of statin was also seen in patients with baseline renal impairment (MH-RR=0.46, 95% CI 0.29 to 0.72, p=0.0008) and also those who were cotreated with NAC (MH-RR=0.46, 95% CI 0.25 to 0.83, p=0.01). Conclusions: Statin pretreatment leads to significant reduction in CIN, and should be strongly considered in all patients who are planned for diagnostic and interventional procedures involving contrast-media administration.